Evaluation of tool wear in EPB tunneling of Tehran Metro, Line 7 Expansion - Amoun, S.; Sharifzadeh, Mostafa; Shahriar, K.; Rostami, J.; Tarigh Azali, S. (Pergamon, 2017)
Wear of cutting tools and other components of the pressurized face tunnel boring machine which come in contact with the muck is an important parameter in soft ground tunneling. This is due to the need for cutterhead inspection and tool maintenance under pressurized conditions or “hyperbaric interventions” which is a time consuming, dangerous, risky, and costly activity. This study investigates the tool wear of an EPB-TBM used in Tehran metro line 7 over the initial 6500 m of tunnel. The ground along the tunnel alignment is mostly alluvial deposits, composed of gravely sand with clay/silt and sandy gravel with clay. In this project, the number of cutting tools replaced were 1169, including 654 rippers, 357 scrapers and 153 disc cutters. In this paper the influence of geological parameters and operational factors on tool wear is examined. The results show that by increasing TBM thrust, earth pressure, and torque, the cutter consumption generally increases. Also, soil conditioning plays an important role in controlling cutter wear, so that the tool wear can be reduced even in coarse-grained soils by improving the soil conditioning parameters. Quantitative analysis of these parameters for this project and a brief discussion of their implications is offered. Also, multiple linear regression analysis was used to seek the best correlation between the cutter wear and ground / opening variables, and correlation coefficient of up to 0.98 have been observed. This highlights the potential of developing models for tool wear prediction by multiple regression, if sufficient data is collected in soft ground tunneling projects.